Influence of cementitious materials and aggregates content on compressive strength of palm kernel shell concrete - Alengaram, U.J.; Jumaat, Mohd Zamin; Mahmud, H. (Journal of Applied Sciences, 2008)
This study reports the effect of cementitious materials, fine and coarse aggregates content on workability and compressive strength of palm kernel shell concrete. Palm kernel shells a by product of the production of palm oil, were used as lightweight aggregates. The following cementitious materials were added: 10 silica fume as additional cementitious material and 5 fly ash as cement replacement on weight of cement. The influence of varying fine aggregate and palm kernel shell contents on workability and compressive strength has been studied. The specimens have been cured under three different curing environments to study the effect on compressive strength. The effect of cementitious materials and curing conditions on compressive strength for a period of 90 days was analyzed. The fresh density of concrete was found to be in the range of 1810 to 1940 kg m-3. The strength of Palm Kernel Shells (PKS) was found to be the primary factor controlling the strength. However, the addition of silica fume was found to have influence on compressive strength. An increase in fine aggregate content and subsequent decrease in PKS content had positive effect on both workability and compressive strength. The 28 day compressive strengths of the mixes containing cementitious materials were found in the range of 26 to 36 MPa. The difference in strength between water cured and specimens cured under controlled environment was found to vary between 3 and 5.